'Before I realised they were all women… I expected it to be more about materials': Art, Gender and Tacit Subjectivity. (February 2016) - Hames, Hannah
Abstract: This article discusses a critical discourse analysis research activity undertaken with a group of undergraduate primary trainees with an art specialism. The research activity involved the use of two contrasting texts discussing the work of Karla Black, Becky Beasley and Claire Barclay. The article explores how the positioning of the two texts affected the student teachers' ability to engage effectively with 'women's art' on a personal and critical level, revealing some highly subjective views and raising questions around intertextuality; particularly how an individual's understanding of contexts, meanings and histories can inform collective interpretation and highlight existing subjectivity. The article subsequently identifies that although students were keen to talk about careful selection of texts, the benefits of using multiple sources and the risks of intertextual and 'subliminal' contamination, they were unable to reflect critically upon their own gendered reading of the texts. It concludes that this may well be a signifier of the problem – that the student teachers did not really see a problem at all.